Psychiatrists’ Attitude Towards Personality Disorder - Tulachan, Pratikchya; Chapagain, Manisha; Dhungana, Saraswati; Pant, Sagun Ballav; Ojha, Saroj Prasad (Journal of Nepal Health Research Council, 2018)
Background: Worldwide mental health professionals have negative attitude towards personality disorder. Aim of this study was to assess the attitudes toward personality disorder among Nepalese psychiatrists. Methods: A cross-sectional survey study was done. Survey questionnaire was developed which consisted of 10 questions to explore the feeling and views regarding personality disorder. It was distributed via e-mail to 80 registered psychiatrist who were randomly selected and responses were analyzed. Results: Results showed only 50% of psychiatrist assessed for personality disorders whereas only 55.6% diagnosed it. Cluster ‘B’personality disorders were most commonly diagnosed personality disorder, 36.1% felt helpless for those patients, 75% felt overall treatment for personality disorder was very difficult and 50% reported they were not competent to care for personality disorder patients. Conclusions: Nepalese psychiatrists were not optimistic towards personality disorder in terms of its recognition, diagnosis and its overall management. Thus, future researches are needed to explore such attitudes in depth in same population.